Safety and Efficacy of Belimumab in Patients with Lupus Nephritis: Open-Label Extension of BLISS-LN Study. Issue 11 (November 2022) - Furie, Richard; Rovin, Brad H.; Houssiau, Frédéric; Contreras, Gabriel; Teng, Y.K. Onno; Curtis, Paula; Green, Yulia; Okily, Mohamed; Madan, Anuradha; Roth, David A.
Visual Abstract: Abstract : Background and objectives: In the BLISS-LN study, belimumab improved kidney outcomes in adult patients with active lupus nephritis. This 28-week open-label extension of BLISS-LN assessed belimumab's safety and efficacy. Design, setting, participants, & measurements: Eligible patients completing BLISS-LN received monthly intravenous belimumab 10 mg/kg plus standard therapy. End points included safety, open-label week 28 primary efficacy renal response (urine protein-creatinine ratio [UPCR] ≤0.7, eGFR no more than 20% below open-label baseline value or ≥60 ml/min per 1.73 m 2, no prohibited medications) and complete renal response (UPCR <0.5, eGFR no more than 10% below open-label baseline value or ≥90 ml/min per 1.73 m 2, no prohibited medications), and UPCR and eGFR by visit. Responses were also analyzed post hoc using the double-blind phase criteria. Results: Of 257 enrolled patients, 255 were treated (safety population: n =123 switched from placebo-to-belimumab; n =132 remained on belimumab); 245 (97%) patients completed the study. Adverse events and serious adverse events were experienced by 62% and 4% of placebo-to-belimumab patients, respectively, and by 70% and 8% of belimumab-to-belimumab patients, respectively. One death occurred in the placebo-to-belimumab group. From open-label baseline to week 28, increases occurred in the proportions of patients achieving primary efficacy renal response (placebo-to-belimumab: from 60% to 67%; belimumab-to-belimumab: from 70% to 75%) and complete renal response (placebo-to-belimumab: from 36% to 48%; belimumab-to-belimumab: from 48% to 62%). Based on double-blind phase criteria, changes also occurred in the proportions achieving primary efficacy renal response (placebo-to-belimumab: from 54% to 53%; belimumab-to-belimumab: from 66% to 52%) and complete renal response (placebo-to-belimumab: from 34% to 35%; belimumab-to-belimumab: from 46% to 41%). The seeming decrease in response rates in the belimumab-to-belimumab groups was attributed to discontinuations/administration of glucocorticoids for non-SLE reasons as opposed to nephritis. Median UPCR and eGFR values were similar at open-label baseline and week 28. Conclusions: No new safety signals were identified, and efficacy was generally maintained throughout the open-label phase. Clinical Trial registry name and registration number: BLISS-LN, NCT01639339